Levetiracetam-induced drug reaction: violaceous discrete maculopapular rash: A case report - Arvinpreet Kour; Ajaydeep Singh (Apollo Medicine)
Introduction:Levetiracetam, a newer second generation antiepileptic, is widely used now a days by physicians, neurologist, and neurosurgeons due to its lesser side effects. The most common side effects known of them are nervousness, irritability somnolence, fatigue, dizziness, and psychosis. Methods: We present a case report with an erythematous to violaceous discrete maculopapular rash presenting bilaterally symmetrical over the extremes to thighs, upper trunk, and the fore head as a side effect of Levetiracetam. Results: There was complete improvement of the pigmentation after stopping the medicine with the use of local kalamine lotions with oral steroids for 14 days. Conclusion: To our knowledge, this is rare as a side effect of levetiracetam. With this information, we will like to get more reports of the side effects of the widely drugs used so frequently.